Management of isolated lateral orbital wall blow-in fracture with optic nerve compression - Time is vision - Moon, Prashant (Indian Journal of Case Reports, 2018)
Blow-in fracture of orbit usually involves floor and medial wall. The lateral wall of an orbit is the strongest wall to prevent blow in.Blow-in fracture of an orbit with severe proptosis and fracture segment pressing on an optic nerve causing impending loss of visionis a very rare entity. Early diagnosis and immediate treatment are very important for restoration of vision in such patient. Here, wereport the case of a post-traumatic lateral orbital wall blow-in fracture in a 22-year-old male. The fracture was compressing the opticnerve, which can cause severe proptosis and may even lead to vision loss if not treated early.